Functional neurological disorder: a qualitative study exploring experiences of psychological services - Staton, Amelia (2023)
Background: Functional Neurological Disorder (FND) is classified as a “disorder of the voluntary motor or sensory system with symptoms including paralysis, tremor, dystonia, sensory disturbance (including visual loss), speech symptoms, and seizures” (Stone et al., 2020, p.1). Individuals with a diagnosis of FND have reported negative and stigmatising interactions with healthcare professionals in medical settings. This is hypothesised to be linked to the etiologic uncertainty and historical context of the condition. Due to current NICE guidelines and service provision, individuals with FND are routinely referred to psychological/mental health services. However, there is no research exploring individuals’ experiences in these settings. The perspectives of those accessing services are essential in understanding and improving the quality of healthcare provision. The aim of this research was to explore experiences of accessing UK psychological services, from the perspective of those with FND.